O vírus se transmite por mensagens instantâneas: a pandemia da covid-19 nas narrativas da família Bolsonaro pelo Telegram - Sousa, Francisco Sérgio Lima de (2024)
The deplatforming policy and content moderation actions by social media platforms have meant that internet personalities with radical discourses are migrating to alternative virtual environments, especially since 2019. Among these is Telegram, which has established itself as the largest hybrid messaging platform in the world and which has the characteristics of being more permissive to extremist content and offering affordances that facilitate the viralization of content. Following this movement, this thesis aims to analyze the characteristics of the communication on this platform of the then Brazilian president Jair Bolsonaro and his three political sons, Flávio, Carlos and Eduardo Bolsonaro, who are among the main leaders of the populist radical right in Brazil. We chose as our period of analysis the first year of these personalities' Telegram channel, from January 2021 to January 2022, a period in which Brazil and the world were facing the covid-19 pandemic and, along with it, the infodemic crisis, in which disinformation gained unprecedented proportions. Because of this, the research corpus will be limited to communications related to the pandemic. In order to understand the proposed subject, we discussed the phenomena of homophily and political polarization and analyzed the advance of the far-right to power. In addition to identifying the characteristics of the content of the posts made by the Bolsonaro clan about Covid-19 on this platform, we sought to understand in what ways radical right-wing populism has influenced communication about the pandemic and in what ways and with what intensity disinformation and denialism have been present. We used a communicational approach to populism to analyze the posts. The methodology applied was content analysis, in a quantitative and qualitative approach. We found that the four members of the family studied here acted in a coordinated way on the platform, with specific roles. The former president developed a more positive agenda, defending his administration, and his children played a more ostentatious role in attacking opponents. The communication of the pandemic was politicized, modulated by the characteristics of populist content and style, notably by the attack on the elites, in Bolsonaro's view, and by the appeal to emotions and negativity in the messages. Disinformation and denialism were present on all the channels, especially those of Carlos and Eduardo Bolsonaro. Discouraging social isolation and encouraging the use of medicines with no proven efficacy were the main disinformation campaigns.